Variation of Carotenoid Content in Different Bitter Melon Cultivars - Won Lee1, Sang; Kwang Kim2, Jae; Romij Uddin3, Md.; Bok Kim3, Yeon; Hoon Kim4, Haeng; Chung5, Eunsook; Lee5, Jai-Heon; Un Park3, Sang (Asian Journal of Chemistry, 2014)
Nine different bitter melon cultivars collected from Japan and Philippines were analyzed to distinguish the levels of three different carotenoids i.e., lutein, a-carotene and b-carotene using HPLC. The carotenoid content varied significantly among the cultivars from the 2 locations. In general, the carotenoid contents in the Philippines cultivar was higher than in the Japanese ones, with the highest content found in Galaxy from Philippines and the lowest in the cultivar Kyushu from the Japanese cultivar. The levels of lutein in the Galaxy cultivar were 2.9 and 2.8 times higher than Kyushu and Trident 357 cultivars, respectively. The cultivar Galaxy from Philippines contained 3.7, 3.1 and 3.0-fold higher a-carotene compared to Kyushu, Sta. Rita Strain. L and Peacock, respectively. The levels of b-carotene in the Galaxy cultivars were 3.9, 2.9 and 2.8 times higher than that of Kyushu, Sta. Rita Strain. L and Peacock, respectively. The results suggest that the bitter melon cultivar Galaxy could potentially be used as a source of carotenoid.